Evaluating the Role of Workplace Environment on Employee Retention in Kathmandu Valley - Hamal, Janga Bahadur; Shrestha, Lasata; Bhandari, Sanjay Raj; Thapa, Hemanta (Nepalese Journal of Business and Management Studies, 2023)
This study investigated how the work environment impacts employee retention at Bhatbhateni supermarket in Kathmandu Valley. The study is guided by a quantitative research approach that involves descriptive, relational, and causal designs. The described data were gathered from 117 samples using a structured questionnaire, and the sampling method used in this study was convenient. The data were analysed using various tools, such as the mean, median, standard deviation, chi-square tests, correlation, and regression analysis. This study established the influence of each factor under working conditions on employee retention. The study revealed a significant positive association between physical, mental, and social work environment and employee retention; that is, high quality working conditions are associated with better retention. In addition, the implications of the study go beyond the specific setting and involve multiple industries and businesses. Creating a comfortable work environment is likely to enhance employees' sense of belonging and well-being, thereby bolstering their commitment to staying with the organization, ultimately fostering higher rates of employee retention, and positively influencing overall organizational performance.